Determinants of performance in professional soccer players at 2 and 5 years after ACL reconstruction - Pinheiro, V. T.; Borque, K. A.; Laughlin, M. S.; Jones, M.; Balendra, G.; Kent, M. R.; Ajgaonkar, R.; Williams, A. (The American Journal of Sports Medicine, 2023)
Background: A number of studies have investigated return to play after anterior cruciate ligament reconstruction (ACLR) in professional soccer players, but it is unclear which factors are associated with a return to the preinjury performance and ability to play over time.